In vivo tumorigenesis by Jaagsiekte sheep retrovirus (JSRV) requires Y590 in Env TM, but not full length orfX open reading frame - Cousens, Chris (2007)
Jaagsiekte retrovirus (JSRV) causes ovine pulmonary adenocarcinoma (OPA), a transmissible lung cancer of sheep. The envelope (Env) glycoprotein protein of JSRV functions as a dominant oncoprotein in vitro and in vivo. An SH2 binding domain (YXXM) in the cytoplasmic tail of the JSRV Env is one of the main determinants of viral transformation at least in vitro. In these studies, we report the first in vivo tests of site-specific mutants of JSRV in their natural host, the sheep. We show that, in vivo, JSRV(21) with the cytoplasmic tail YXXM mutated to DXXM did not cause disease nor detectable infection, indicating that this motif is absolutely required for virus replication and possibly transformation in vivo. In contrast, mutation of the JSRV open reading frame orfX, for which no function has yet been attributed, did not alter the disease induced by JSRV(21).